Analysis of the convergence of the Safety Attitudes Questionnaire and the Hospital Survey on Patient Safety Culture - Ana Laura Olsefer Rotta; Lucas Paulo de Souza; Manuella dos Santos Garcia Vanti Carvalho; Amanda Pestana da Silva; Andrea Gonçalves Bandeira; Janete de Souza Urbanetto (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze patient safety culture from nursing professionals' perception at a university hospital, by assessing the convergence between the Safety Attitudes Questionnaire and the Hospital Survey on Patient Safety Culture. Methods: a cross-sectional study, with 434 nursing professionals. Data collection took place through the application of both instruments. Descriptive and inferential statistics were used. Results: in the Hospital Survey on Patient Safety Culture, the "teamwork within the units" dimension was considered a strong area of patient safety. In the Safety Attitudes Questionnaire, the "job satisfaction" and "perception of stress" domains reached the score for a good safety culture. Patient safety culture perception is correlated, in both instruments, with high magnitude. Conclusions: the two instruments converge towards a similar assessment of patient safety culture.